Tradisi Maantar Patalian pada Perkawinan Masyarakat Adat Banjar Kalimantan Selatan (Telaah Antropologis dan Sosiologis) - Arie Sulistyoko; Anwar Hafidzi (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2020)
The marriage in Indonesia is usually done with customary rules, one of which is the Banjar tribe who still has a strong culture in the process of marriage ceremony. In practice in Indonesia, in addition to following religious regulations, tradition also becomes important, as practiced by the people of Banjar when conducting marriages filled with various customs both before, shortly or after marriages are conducted. The application of the procession, the benchmark is honesty itself, where if the total honesty requested is not met by men, then the girl's family prefers to cancel it. In this condition, the local people's customary approach is the benchmark in the traditional Banjar marriage system